BASIC CONCEPTS AND ESSENCE OF THE CLASSIFICATION OF MIGRATION AND MIGRATION PROCESSES TODAY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article presents the basic concepts and essence of the classification of migration and migration processes. The directions of migration in the world are studied and this process continues. Although migration is growing rapidly in our country, few studies have been conducted on this area, it has been studied little. Scientific works and projects on migration in the world and in Uzbekistan are scientifically justified.